Peripheral blood lymphocyte phenotype can predict rejection episodes after orthotopic liver transplantation - Perdigoto, R. (1999)
http://www.sciencedirect.com/science/article/B6VJ0-3XFKHGV-3V/1/21ca47d4f3a98743181f2d76010e13c3